(untitled) - Prof. Dr. Susanne Elsen; Prof. Dr. Markus Gmür; Prof. Dr. Dorothea Greiling; Silke Helfrich; Prof. Dr. Winfried Kluth; Prof. Dr. Remi Maier-Rigaud; Prof. Dr. Ulf Papenfuß; Barbara Sak; Prof. Dr. Christina Schaefer; Prof. Dr. Michaela-Maria Schaffhauser-Linzatti; Prof. Dr. Frank Schulz-Nieswandt; Prof. Dr. Dieter K. Tscheulin (Z'GuG Zeitschrift für Gemeinwirtschaft und Gemeinwohl, 2023)
The Zeitschrift für Gemeinwirtschaft und Gemeinwohl (Z'GuG) is an interdisciplinary academic journal with relevance for professional practice (business, politics, civil society). The journal is published as a new series of the Zeitschrift für öffentliche und gemeinwirtschaftliche Unternehmen (ZögU) - Journal for Public and Nonprofit Services. The thematic focus is on public economics in its diversity of sponsors, administrative theory, the social economy, the third sector, cooperatives, as well as topics of importance to civil society such as communalization, neighborhood and district concepts, network development, and social space building. The Z'GuG is open to fundamental theoretical and methodological discussions and takes up topics that require a cultural-scientific, but also philosophical opening, including the social (medical, nursing, educational, etc.) care debates, gender and other diversity controversies, commons theory, and gift and reciprocity research. From these openings, Z'GuG is dedicated to the meta-theme of the common good.